PENERAPAN STRATEGI PEMBELAJARAN TASK BASED LANGUAGE LEARNING DALAM MENINGKATKAN KETERAMPILAN MENULIS TEKS DESKRIPTIF BAHASA PERANCIS - Anshary, Dinan; Mulyadi, Yadi; Mutiarsih, Yuliarti (Jurnal Pendidikan Bahasa dan Sastra, 2019)
Â Today there are so many learning strategies to support teaching and learning activities. One of the learning strategies that can be applied in writing skills is Task Based Language Learning. This research aims to measure the level of student mastery of descriptive text writing skills before and after the use of Task Based Language Learning strategies; measure the effectiveness of the implementation of Task Based Language Learning, and; obtain information about the implementation of Task Based Language Learning. The method used in this research was a pre-experimental. Meanwhile, the research design was one group pre-test and post-test design. The research findings explained that the use of Task Based Language Learning can improve studentsâ€™s descriptive text writing skills. This is proven by an increase in the average value obtained by students. The average score in the pre-test was 60.8 while the post-test average score increased by 74.88. Then based on the overall questionnaire data analysis, the application of this learning strategy contributed positively to the learning of descriptive French writing skills.